Coupling PtNi Ultrathin Nanowires with MXenes for Boosting Electrocatalytic Hydrogen Evolution in Both Acidic and Alkaline Solutions. Issue 12 (20th February 2019) - Jiang, Yi; Wu, Xingqiao; Yan, Yucong; Luo, Sai; Li, Xiao; Huang, Jingbo; Zhang, Hui; Yang, Deren
Abstract: Developing an efficient electrocatalyst for the hydrogen evolution reaction (HER) working in both acidic and alkaline solutions is highly desirable, but still remains challenging. Here, Pt x Ni ultrathin nanowires (NWs) with tunable compositions ( x = 1.42, 3.21, 5.67) are in situ grown on MXenes (Ti3 C2 nanosheets), serving as electrocatalysts toward HER. Such Pt x Ni@Ti3 C2 electrocatalysts exhibit excellent HER performance in both acidic and alkaline solutions, with the Pt3.21 Ni@Ti3 C2 being the best one. Specifically, Pt3.21 Ni@Ti3 C2 achieves record‐breaking performance in terms of lowest overpotential (18.55 mV) and smallest Tafel slope (13.37 mV dec −1 ) for HER in acidic media to date. Theory calculations and X‐ray photoelectron spectroscopy analyses demonstrate that the coupling of MXenes with the NWs not only approaches the Gibbs free energy for hydrogen adsorption close to zero through the electron transfer between them in acidic media, but also provides additional active sites for water dissociation in alkaline solution, both of them being beneficial to the HER performance. Abstract : Ultrathin PtNi alloy nanowires are in situ synthesized on MXene nanosheets. The coupling of MXenes with PtNi nanowires not only approaches the Gibbs free energy for hydrogen adsorption close to zero through the electron transfer in acidic media, but also provides additional active sites for water dissociation in alkaline solution, boosting the hydrogen evolution reaction performance.